Learning the Emotional Rules of Teaching: A Foucauldian Analysis of Ethical Self-formation in Pre-service Teacher Education - Karnovsky, Saul Adam (Curtin University, 2020)
The thesis explores how pre-service teachers learn the emotional norms of the profession. Using a post-structural theoretical frame to analyse longitudinal qualitative data, examination is focused upon how professional subjectivities of pre-service teachers are shaped during an initial teacher education course. Learning emotional rules produces both professionally normalised emotional conduct as well as practices of self-care as participants cultivate a teaching persona. The thesis argues for a rethinking and re-theorising of emotions in teacher education.